Equilibrium, kinetics and isotherm studies of Cadmium (II) adsorption from aqueous solution utilizing Cane Papyrus - Alatabe, Mohammed Jaafar Ali (جامعة الوادي - university of el oued, 2021)
Cadmium(II) ions is a very toxic element known to cause detrimental effects to human health even at very low concentrations. Cane Papyrus was prepared form the marsh in south of Iraq, as adsorbent to Cadmium(II) ions adsorption from aqueous solution. Completed the analysis by using Fourier transform infra-red and notes presence of amino (–NH), carbonyl (–C=O) and hydroxyl (–OH) functional groups. Batch experiments were performed on simulated aqueous solutions under optimized conditions of adsorbent dosage, contact time, pH and initial Cadmium(II) ions concentration at 25Co. The Freundlich isotherm model more suitably described the adsorption process than the Langmuir model with linearized coefficients of 0.986 and 0.9733, respectively. Pseudo-second order kinetic equation best described the kinetics of the reaction. Furthermore, 1M HCl was a better desorbing agent than 1M NaOH and de-ionized water. The experimental data obtained demonstrated that Cane Papyrus can be used as a suitable adsorbent for Cadmium(II) ions removal from wastewater.
Article
Keywords: Cadmium(II) ions; Cane Papyrus; Equilibrium; Kinetics